Analisis Pendidikan di Arab Saudi dan Keunikannya Dibandingkan Pendidikan di Indonesia - Witta Perdana Putri; Mislaini Mislaini; Ulfa Aulia (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This article discusses the analysis of the education system in Saudi Arabia and compares it with the education system in Indonesia. Education in Saudi Arabia has unique characteristics that are influenced by cultural, religious and national policy contexts. The education system in Saudi Arabia is very focused on Islamic values ​​with a curriculum that is integrated with religious teachings, especially in the fields of Al-Qur'an and Sharia studies. In contrast, the education system in Indonesia, although also applied to religious values, shows a more pluralistic and inclusive approach due to the cultural and religious diversity in this country. This article also explores differences in educational structures, teaching methods, the role of government, and gender policies in education. This analysis provides insight into the advantages and challenges of each education system, as well as their relevance in forming a competitive generation at the global level.